Psikologi Perkembangan Moral Anak Usia Dini Berbasis Nilai-Nilai Kasih Sayang - Milda; Syahrul Saputra; Martina (Prodi PIAUD STAI AL-GAZALI BONE, 2025)
Early childhood moral development is an important aspect in character formation from an early age. Morality is not only related to understanding right and wrong, but also includes children's ability to show empathy, caring, and mutual respect. One effective approach to supporting early childhood moral development is through instilling compassionate values in the educational process. This study aims to examine early childhood moral development from a developmental psychology perspective, emphasizing the role of compassionate values in social interactions and learning. The research method used is a literature review by analyzing various literature sources in the form of relevant books and scientific journals. The results of the study indicate that the application of compassionate values through teacher role models, positive behavioral habits, and the creation of a safe and comfortable learning environment can help children internalize moral values gradually. Compassionate values also play a role in increasing prosocial behavior and reducing negative behavior in early childhood.